2016
DOI: 10.1149/2.0281606jes
|View full text |Cite
|
Sign up to set email alerts
|

Selective Sensing of Bisphenol A and Bisphenol S on Platinum/Poly(diallyl dimethyl ammonium chloride)-diamond Powder Hybrid Modified Glassy Carbon Electrode

Abstract: In this work, a new platinum (Pt) nanoparticles-functionalized poly(diallyl dimethyl ammonium chloride) (PDDA)-diamond powder (DMP) composite-modified glassy carbon electrode (GCE) was fabricated for electrochemical sensing of the selective or simultaneous determination of bisphenol A (BPA) and bisphenol S (BPS). The Pt/PDDA-DMP hybrid was characterized by Scanning electron microscopy, Transmission electron microscope, Fourier transform infrared, X-ray diffraction analyzer. This hybrid exhibited remarkable ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(14 citation statements)
references
References 57 publications
1
13
0
Order By: Relevance
“…The linear regression equation is depicted as I = 0.1481C BPA − 0.2674 (R 2 = 0.9978), and the limit of detection (LOD) is down to 0.19 μM (S/N = 3) by standard formula. 63 The as-constructed sensor exhibits a wider linear range and lower LOD as compared with the previously reported research for the detection of BPA (Table S1), such as platinum/poly(diallyl dimethyl ammonium chloride)−diamond powder (Pt/PDDA−DMP) 68 and silver NPs−exfoliated graphite (Ag−EG) 2 . Based on the data, the G-PtCoNi/N-PCFs are certified as feasible for the determination of BPA.…”
Section: Electrochemical Behaviors Of the G-ptconi/n-pcf-basedmentioning
confidence: 75%
“…The linear regression equation is depicted as I = 0.1481C BPA − 0.2674 (R 2 = 0.9978), and the limit of detection (LOD) is down to 0.19 μM (S/N = 3) by standard formula. 63 The as-constructed sensor exhibits a wider linear range and lower LOD as compared with the previously reported research for the detection of BPA (Table S1), such as platinum/poly(diallyl dimethyl ammonium chloride)−diamond powder (Pt/PDDA−DMP) 68 and silver NPs−exfoliated graphite (Ag−EG) 2 . Based on the data, the G-PtCoNi/N-PCFs are certified as feasible for the determination of BPA.…”
Section: Electrochemical Behaviors Of the G-ptconi/n-pcf-basedmentioning
confidence: 75%
“…[15][16][17][18][19] Zheng et al demonstrated platinum nanoparticles (Pt-NP) modified poly(diallyl dimethyl ammonium chloride)-diamond based glassy carbon electrode for the electrotechnical detection of bisphenol S and BPA with a sensitivity range of 10-60 (2.3 −14 µg mL −1 ) and 5-30 µm (1.1 −6.8 µg mL −1 ), respectively. [20] Another study demonstrated highly sensitive tyrosinase immobilized diamond electrode-based electrochemical sensors for the detection of BPA in the concentration range of 2.3 pg mL −1 to 23 ng mL −1 . [19] Dong et al reported a highly conductive electrochemical sensor modified with graphite NP with a limit-of-detection (LOD) of 10 pg mL −1 BPA.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, another technique based on electrochemical characterization has been widely applied into BPA determination. Because of their fast responses and real-time detections, the electrochemical BPA sensors have been reported by many groups. Most of the devices are based on the construction or modification of electrodes with nanoparticles (NPs), carbon nanotubes (CNTs), graphene, and other nanomaterials to increase their surface area, conductivity, and electrochemical activity. These techniques can improve the sensitivity of BPA detection and decrease the operational voltage of the devices.…”
Section: Introductionmentioning
confidence: 99%
“…These techniques can improve the sensitivity of BPA detection and decrease the operational voltage of the devices. Specifically, Zheng et al presented the glassy carbon electrodes functionalized with the Pt NP-modified poly­(diallyl dimethyl ammonium chloride)–diamond composite for the electrochemical sensing of BPA and bisphenol S with the sensitivity range of 5–30 μM (1.1–6.8 μg/mL) and 10–60 μM (2.3–14 μg/mL), respectively . Another highly sensitive electrochemical BPA sensor was realized with the immobilization of tyrosinase onto a diamond electrode that was also modified with diazonium, and CNTs, which demonstrated a large linear detection range between 10 pM and 100 nM (2.3 pg/mL to 23 ng/mL).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation